Improvement the modelling of atmospheric effects for electronic distance measurement (EDM): analysis of air temperature, atmospheric pressure and relative humidity of air - Sabzali, Mansoor; Jazirian, Iraj (Geodesy and Cartography, 2022)
The atmosphere is an undeniable source of error for any geodetic instruments. Surveyors require to have an accurate approximation of distance measurements in order to accurately determine the 3D coordinate of points. Electronic Distance Measurements (EDMs) are employed to measure accurate range to the target. They are typically functioning by laser in the domain of light or near infrared of electromagnetic spectrum (EM). Snell’s law has proved propagating wave through passing the different layers of atmosphere is deviated. This phenomenon is called the refractivity of wave. This deviation is introduced by different intersection between the beam and the object surface at different epochs of atmospheric change. By possessing the knowledge of group refractive index, it is possible to estimate the value of correction in ppm for measured distances caused by the variations in atmospheric elements. The changes in three components of air, temperature, pressure and humidity, in this study will be considered.